Changes in the prevalence, genotypes and antimicrobial resistance phenotypes of non‐typhoidal Salmonella recovered from mail‐order hatchling poultry sold at US feed stores, 2013–2015. (30th October 2017) - Sharma, A.; Erdman, M. M.; Muñoz‐Vargas, L.; Mollenkopf, D. F.; Habing, G. G.
Summary: Every year, multiple outbreaks of salmonellosis in humans are linked to contact with mail‐order chicks and ducks. The objective of this study was to describe the temporal changes in the prevalence of serovars, genotypes and antimicrobial resistance (AMR) phenotypes of non‐typhoidal Salmonella (NTS) recovered from shipped boxes of mail‐order hatchling poultry in the United States during 2013 to 2015. In each year, a sample of feed stores belonging to a single national chain participated in the study. The store employees submitted swabs or hatchling pads from hatchling boxes and shipment tracking information of the arriving boxes to the investigators. NTS was cultured from the samples and isolates were sent to the National Veterinary Services Laboratories (Ames, IA) for serotyping, pulsed‐field gel electrophoresis (PFGE) and AMR phenotyping. The PFGE patterns of Salmonella serovars isolated from hatchling boxes were compared with those from human outbreaks of salmonellosis linked to live poultry contact. The box‐level prevalence of NTS was significantly higher in 2015 compared to 2014. Also, the population of Salmonella serovars recovered in 2015 was more diverse and substantially different from those recovered in the previous two years. Of PFGE patterns recovered from hatchling boxes, seven distinct patterns in 2015, three in 2014 and four in 2013 were indistinguishable from the PFGE patterns of human outbreaks‐associated strains in the respective years. Importantly, a significant positive correlation was found between the box‐level prevalence of PFGE patterns and the number of human illnesses associated with the same patterns. Also, the proportion of multidrug‐resistant isolates was higher in 2014 and 2015 compared to that in 2013. The results demonstrate that shipments of mail‐order hatchling poultry are frequently contaminated with Salmonella genotypes indistinguishable from human outbreaks‐associated strains each year, and control efforts at hatchery level are likely to have an important public health impact.